Mewujudkan Ekonomi Impian Keluarga yang Terukur Melalui Program Perencanaan Keuangan Sakinah di Kelurahan Sumber Rejo - Alifiana Sabrina Febrianti; Mita Nur Maulidah; Risma Aulia; Sihmurni Fadhillah (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Financial planning is an effort used to allocate a family's income and expenses properly and correctly to realize the family's financial goals (Ridwan, 2015). The aim of this activity is to increase understanding of sakinah financial management among PKK mothers in Sumber Rejo Village, to provide innovative ideas for PKK mothers who have MSME businesses on how they manage finances for their families and businesses. The implementation method for Innovation Development (PI) that will be carried out is in stages that are arranged systematically. The result of this activity was that group 14 was able to complete mentoring activities and seminars in the Sumberrejo sub-district.